2000
DOI: 10.1038/sj.cgt.7700146
|View full text |Cite
|
Sign up to set email alerts
|

Construction and function of a recombinant adenovirus encoding a human aquaporin 1-green fluorescent protein fusion product

Abstract: Transfer of the human aquaporin 1 (hAQP1) gene provides a novel way to potentially correct the severe salivary hypofunction associated with therapeutic radiation for head and neck cancer. To facilitate the study of individual cells transduced with this gene, we have designed a fusion product of the hAQP1 and jellyfish green fluorescent protein (GFP ) cDNAs. An expression plasmid, pACCMVhAQP1GFP, and a recombinant adenovirus, AdhAQP1GFP, encoding this fusion product were constructed. Both the recombinant plasmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Aquaporins tagged with a fluorescent protein at the N terminus are known to retain their functional activity (19,20). The fluorescence of the fusion protein indicated its location in the plasma membrane (Fig.…”
Section: Expression Of Aqp1 and Yfp-aqp1 In Hek293mentioning
confidence: 99%
“…Aquaporins tagged with a fluorescent protein at the N terminus are known to retain their functional activity (19,20). The fluorescence of the fusion protein indicated its location in the plasma membrane (Fig.…”
Section: Expression Of Aqp1 and Yfp-aqp1 In Hek293mentioning
confidence: 99%
“…To determine whether the induction of REG Iα mRNA was caused by the activation of transcription, a 1216-base pair fragment containing 1190-base pair of the promoter region (−1190∼+26) of the human REG Iα gene [73] was fused to the luciferase reporter gene of pGL3-Basic vector and transfected into human NS-SV-DC and rat A5 [74,75] salivary ductal cells using the Lipofectamine™ 2000 reagent. Six hours after transfection, cells were incubated with IL-6 or IL-8 for 24 h, and cell extracts were prepared for luciferase assay.…”
Section: Activation Of Reg Iα Gene Promoter By Il-6mentioning
confidence: 99%
“…To determine whether the increase of REG Iα mRNA was caused by the activation of transcription, a 1216-bp fragment containing 1190-bp of the promoter region of the human REG Iα gene was fused to the luciferase gene and transfected into human NS-SV-DC and rat A5 [86,87] salivary ductal cells. We found that IL-6 stimulation significantly enhanced the REG Iα promoter activity not only in NS-SV-DC cells but also in A5 cells.…”
Section: Gene Expression Of Reg Iα As An Auto-antigenmentioning
confidence: 99%